Birdi Golf Apparel : flying high or swinging low? - Gaylard, Alison; Beder, Laurence ([London] : SAGE, 2016)
In December 2008, Charlene Lewison, marketing director of the Johannesburg-based family business, Birdi Golf Apparel, surveyed the company's well-stocked shelves with pride - but also with a growing sense of unease. In the past 12 years, Birdi had become an established brand on both the professional and amateur golf circuits in South Africa. In recent months, however, sales had started to slow as the economic crisis took effect, and Lewison knew the time had come to rethink her company's marketing strategy and planning. Should the company look at new products, or perhaps new market segments? Should it retain its `niche' status or broaden its base, or should it try to penetrate its current corporate business further?
Originally Published in: Gaylard, A., & Beder, L. (2009). Birdi Golf Apparel: Flying High or Swinging Low? WBS-2009-18. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Birdi Golf Apparel (Firm); Strategic planning -- Case studies; Leadership -- Case studies; Marketing -- Management -- Case studies